Issues of contraception in rheumatic diseases: current status of the problem and perspectives - T. S. Panevin; A. A. Smetnik; T. V. Dubinina (Современная ревматология)
Contraception is an important aspect of reproductive health in patients with rheumatic diseases. This is primarily due to the fact that in most immuneinflammatory rheumatic diseases (IRD) pregnancy must be planned. On one hand, the presence and activity of IRD can influence the course of the pregnancy, but on the other hand, pregnancy, which is accompanied by changes in general hormonal levels, is often a factor that alters the activity of IRD. Some patients take medication with potentially teratogenic effects. Planning a pregnancy during IRD can contribute to its optimal progression and minimize the risks of exacerbation of IRD. Given the wide range of barrier and hormonal contraceptives currently in use and the introduction of new drugs into clinical practice, data on the possibility of their use are of particular importance to rheumatologists in practical healthcare.